Activity of BKM120 and BEZ235 against Lymphoma Cells. (18th October 2015) - Civallero, Monica; Cosenza, Maria; Pozzi, Samantha; Bari, Alessia; Ferri, Paola; Sacchi, Stefano
Abstract : Non-Hodgkin lymphomas encompass a heterogeneous group of cancers, with 85–90% arising from B lymphocytes and the remainder deriving from T lymphocytes or NK lymphocytes. These tumors are molecularly and clinically heterogeneous, showing dramatically different responses and outcomes with standard therapies. Deregulated PI3K signaling is linked to oncogenesis and disease progression in hematologic malignancies and in a variety of solid tumors and apparently enhances resistance to antineoplastic therapy, resulting in a poor prognosis. Here, we have evaluated and compared the effects of the pan-PI3K inhibitor BKM120 and the dual PI3K/mTOR inhibitor BEZ235 on mantle, follicular, and T-cell lymphomas. Our results suggest that BKM120 and BEZ235 can effectively inhibit lymphoma cell proliferation by causing cell cycle arrest and can lead to cell death by inducing apoptosis and autophagy mediated by ROS accumulation. Despite great advances in lymphoma therapy after the introduction of monoclonal antibodies, many patients still die from disease progression. Therefore, novel treatment approaches are needed. BKM120 and BEZ235 alone and in combination are very effective against lymphoma cells in vitro . If further studies confirm their effectiveness in animal models, they may be promising candidates for development as new drugs.